Working Capital Management in Efforts to Improve Profitability and Competitiveness of MSMEs - Yusbardini Yusbardini (CV. Proaksara Global Transeduka, 2025)
Effective and efficient working capital management is necessary for every MSME so that the company's operational activities can increase profitability and competitiveness. Good working management can enable MSMEs to manage inventory, improve product marketing, and respond quickly to market changes, thereby increasing the competitiveness and profitability of MSMEs. The purpose of this service is to provide counselling on working capital management to Vezara MSMEs in PGC Cililtan East Jakarata. This training aims to make Vezara MSMEs understand working capital management so that cash can be used as efficiently as possible, selling goods as quickly as possible, avoiding liquidity problems and increasing production capacity. MSME owners must really know effective and efficient working capital management because this is the key to successful MSME operational activities in producing profitability and competitiveness. Therefore, the PKM Team needs to provide this training to help Vezara MSMEs make a profit.